Entrepreneurship, Microfinance and Social Relation: An Empirical Analysis of Women's Perceptions - Rakhal, Dhaneshwar (Journal of Nepalese Business Studies, 2016)
Women can become active entrepreneurs, if they are provided with easy access to the financial services. Microfinance provides access to financial services that can help women to improve their economic life by both promoting opportunities of entrepreneurship and facilitating for the women empowerment. It means microfinance can create opportunities for economic wellbeing, and make them economically independent. Accordingly, this paper explores the women's experiences on microfinance schemes aimed at creating independent women entrepreneurs. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 116-125